Influência dos sistemas de informação (SI) fornecidos pelo APL de software no sudoeste paranaense sob a perspectiva da inovação organizacional - Ferreira, Rafael Henrique Mainardes (2015)
This study aims to evaluate the influence of the Information Systems (IS) provided by the Software‟s Cluster of Southwest‟s Paraná for the region in question, guided by the precepts of innovation, specifically, organizational innovation. Through semi-structured questionnaires, it was possible to conduct interviews with managers and business users who purchased the Software companies that make up the cluster in question. After the search and selection of companies to be researched - from the data collected by the Information Technology Center (NTI) - it was possible to contact the respondents and hear the testimonials about the product innovation, processes, organizational structures to conceptualize companies in the markets in which they operate, and subsequently verify the acceptance and development of Software acquired in companies in order to seek evidence supporting organizational innovation. After surveying of the statements, it was possible to compare some data on the vision of managers and users of the systems found by checking the convergence or divergence of views on the matter and consider jointly, user acceptance for this new form of routine processes. The work, in addition to the objectives achieved, considering the analysis of factors that place the southwest of the Software APL Paraná as a developer of activities that not only seek the negotiation, development, purchase and sale of products and systems, but also as an important link between the company and the customer, being guided by the needs and difficulties encountered after applying novelty in business processes. The research showed that the APL in question, therefore, is able to act as a strong developer of social practices, setting the business external environment and modifying the internal structures in order to assist those involved in the new search, accelerating processes and approaching the stakeholders.